The use of the item agora in the discourse from the city of Natal. - Valdecy Oliveira Pontes; Rosângela Bessa Vidal; Francisco Clébio Figueiredo (Travessias, 2017)
In this work we adopted the postulates of the American functionalist theory, denominated Use-Centered Functional Linguistics – LFCU, considering linguistic change by means of discursivization and grammaticalization in a synchronic perspective. We approach the functioning of the expression agora in the discourse from the city of Natal with samples from the corpus DG (1998). Our goal is to analyze the multifunctionality of the item agora in the several pragmatic-discursive contexts. Thus, we analyze each context of use of this adverb considering occurrence and categorize the data by its range, variation and change